Electrochemical studies of a high voltage Na4Co3(PO4)2P2O7–MWCNT composite through a selected stable electrolyte. Issue 27 (22nd April 2020) - Kumar, P. Ramesh; Essehli, R.; Yahia, H. B.; Amin, R.; Belharouak, I.
Abstract : Na4 Co3 (PO4 )2 P2 O7 –MWCNT composites in 1 M NaPF6 in EC:DMC electrolytes deliver stable discharge capacities of 80 mA h g −1 and 78 mA h g −1 at normal and elevated temperatures, respectively. In a full cell configuration vs. NaTi2 (PO4 )3 –MWCNT, they deliver an initial discharge capacity of 78 mA h g −1 at 0.2C rate. Abstract : Cathode materials that operate at high voltages are required to realize the commercialization of high-energy-density sodium-ion batteries. In this study, we prepared different composites of sodium cobalt mixed-phosphate with multiwalled carbon nanotubes (Na4 Co3 (PO4 )2 P2 O7 –MWCNTs) by the sol–gel synthesis technique. The crystal structure and microstructure were characterized by using PXRD, TGA, Raman spectroscopy, SEM and TEM. The electrochemical properties of the Na4 Co3 (PO4 )2 P2 O7 –20 wt% MWCNT composite were explored using two different electrolytes. The composite electrode exhibited excellent cyclability and rate capabilities with the electrolyte composed of 1 M sodium hexafluorophosphate in ethylene carbonate:dimethyl carbonate (EC:DMC). The composite electrode delivered stable discharge capacities of 80 mA h g −1 and 78 mA h g −1 at room and elevated (55 °C) temperatures, respectively. The average discharge voltage was around 4.45 V versus Na + /Na, which corresponded to the Co 2+/3+ redox couple. The feasibility of the Na4 Co3 (PO4 )2 P2 O7 cathode for sodium-ion batteries has been confirmed in real time using a full cell configuration vs. NaTi2 (PO4 )3 –20 wt% MWCNT, and it delivers an initial discharge capacity of 78 mA h g −1 at 0.2C rate.